ASSOCIATION BETWEEN EXCLUSIVE BREASTFEEDING AND STUNTING IN CHILDREN : A SYSTEMATIC REVIEW - M. Hadi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Several epidemiological studies have shown that breastfeeding is not optimal, the wrong way of feeding, repeated illnesses during toddlers will affect the incidence of stunting. Aim: The goal of this study is to showed the association association between exclusive breastfeeding and stunting in children. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: We located 672 articles in the PubMed database and 561 in the SagePub database as a result of our search. The search for the final 12 months of 2013 returned a total of 109 PubMed articles and 72 SagePub articles. 25 papers in all were compiled, with thirteen coming from PubMed and twelve from SagePub. There are four studies that made the cut. Conclusion: According to the findings of research, there is a significant connection between exclusive breastfeeding and stunting.